3T3-L1 세포분화 중 지방축적 및 활성산소종 생성에 대한 국내 산림자원 5종 추출물의 효과 - 최선일(Sun-Il Choi); 이종석(Jong Seok Lee); 이사라(Sarah Lee); 이혜진(Hye Jin Lee); 여주홍(Joohong Yeo); 조봉연(Bong-Yeon Cho); 이진하(Jin-Ha Lee); 김재민(Jae-Min Kim); 정태동(Tae-Dong Jung); 최승현(Seung-Hyun Choi); 김종예(Jong-Yea Kim); 강석남(Suk-Nam Kang); et al. (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
This study investigate the effects of extracts of five species of Korean native forest plants on lipid accumulation and reactive oxygen species (ROS) production during the differentiation of 3T3-L1 cells. Our results show that Korean native forest plants extracts significantly reduced lipid accumulation and ROS production during adipogenesis in 3T3-L1 cells. Especially, Rubus coreanus Miq. was most effective in the inhibition of lipid accumulation and ROS production at a concentration of $100μg/mL$. Moreover, Rubus coreanus Miq. extracts significantly inhibited adipocyte differentiation, which is dependent on down-regulation of peroxisome proliferator-activated receptor gamma, CCAAT/enhancer-binding protein alpha, and adipocyte-specific fatty acid binding protein, a key adipogenic transcription factor. Therefore, these results suggest that Rubus coreanus Miq. might be a valuable source of bioactive compounds with anti-adipogenic activity. 본 연구는 국내 산림자생 식물 추출물 5종(밤나무, 진달래, 산수유, 복분자딸기, 갈참나무)에 대한 지방세포 분화 억제 및 활성산소종(ROS) 생성 억제 효능을 평가하였다. 지방세포 분화 중 세포 내 지방축적 및 ROS 생성량을 비교한 결과, 국내 산림 식물 5종 모두 지방축적량 및 ROS 생성량을 농도 유의적으로 감소키는 것으로 나타났다. 특히 복분자딸기 추출물을 처리한 지방세포에서 지방 축적 및 ROS 저감에 가장 크게 나타났으며 양성대조군으로 사용된 N-acetyl-L-cysteine과 유사한 결과를 나타내었다. 또한, 복분자딸기 추출물을 처리함으로써 지방세포의 분화를 조절하는 전사인자인 $PPARγ$, $C/EBPα$ 및 aP2 발현이 억제됨을 확인하였다. 국내 산림 식물 5종 추출물은 천연물에서 유래한 항비만 및 항산화 활성 기능성식품 소재로 활용 가능할 것으로 생각한다.